Selective Feeding by a Predatory Sea Star Across a Depth Gradient in Northern Patagonia, Chile - Garrido, Ignacio; Pardo, Luis Miguel; Johnson, Ladd E.; Schories, Dirk (Frontiers in Marine Science, 2021)
Sea stars often function as keystone predators in food webs of intertidal and subtidal communities, especially in temperate and sub-polar regions. In South America the sea star Cosmasterias lurida is distributed along both the Atlantic and Pacific coasts of Patagonia and is one of the most conspicuous and abundant benthic predators in the shallow subtidal zone (<25 m). Its feeding strategy and prey selection are, however, still poorly known. This study describes the feeding behavior of C. lurida at a site in the Seno del Reloncaví (Chile), assessing its abundance, size and prey selection in the field relative to observed prey abundance and size along a bathymetric gradient. We hypothesized that C. lurida is a generalist predator, feeding on suitable prey according to their availability. However, we found that this predator only consumed a limited number (7 of 48) of potential prey species, primarily the slipper limpets Crepipatella spp. and the mussels Aulacomya ater and Mytilus chilensis. Electivity analysis revealed a clear preference for one mussel (A. ater) but not the other (M. chilensis) as well as depth-dependent selectivity for the slipper limpets, which changed from avoidance to preference with increasing depth. Sea star densities varied with depth, peaking between depths of 5 and 10 m, but the size of sea stars and the size of their prey did not vary significantly along a depth gradient. No significant correlations were found with the most commonly selected prey. These results would indicate that while this predator may be a generalist–opportunist, its feeding behavior is context-dependent and its high selectivity for certain species suggests that this sea star plays a key role structuring subtidal benthic communities in Patagonia.